Classes coopératives multi-âges : une approche alternative des différenciations pédagogiques - Laurent Lescouarch (Éducation et Socialisation)
As part of a collaborative research in participatory observation in four multi-age classes in elementary schools in France, this contribution studies an approach to pedagogical differentiation that is still not widely disseminated in teaching practices in France: entry through the construction of a personalized and supportive environment in cooperative classes. The survey puts into perspective the systemic modelling of the organisation of work in these classes (inspired by Freinet and institutional pedagogies) and the different practices of pedagogical differentiation identified in the activity of teachers, in order to consider their interest and the limits for a better consideration of the learning needs of pupils.